Hemophilia in pediatric age - Cristina Elena Singer; Carmen Simona Cosoveanu; Jaqueline Abdul-Razzak; Alina Popescu; Iulian Iliescu; Maria Madalina Singer; Mihaela Popescu; Alin Iulian-Silviu Popescu (Amaltea Medical Publishing House, 2023)
Hemophilia represents the most common inherited bleeding disorder linked to the X chromosome, which, if not properly treated, can lead to lifelong disabilities. This article presents the cases of 18 patients with hemophilia admitted between 2006-2022 to the Pediatric Oncohematology Department, Clinic II Pediatrics, Emergency County Hospital Craiova. Clinical and evolutionary aspects of the hospitalized patients are presented, including age at the time of diagnosis, heredo colateral history, symptoms at onset, clinical manifestations during the course of hospitalization, complications and prophylactic treatment.